UTILIDAD DEL AGAR CROMOCANDIDA PARA EL DIAGNOSTICO DIFERENCIAL DE CANDIDA spp AISLADAS DE MUESTRAS VAGINALES - José Luis Gatica M.; Iván Goic B.; María Angélica Martínez T.; Iván Reid S. de O.; Pablo Céspedes P.; María Cecilia Arias E.; Alfredo Ovalle S.; Hugo Muster O. (Permanyer, 2002)
Las especies de Candida, es la segunda mayor frecuencia de vulvovaginitis. En los últimos años Candida no albicans, aumentó su frecuencia y el diagnóstico es difícil. El empleo de Agar Cromocandida, facilite la diferenciación entre Candida albicans y Candida spp. El uso combinado de medio cromogénico y el test del tubo, permite identificar los diferentes tipos de Candida Candida species are the second most common cause of vulvovaginitis. In recent years an increase in the prevalence of Candida non-albicans species has been observed in some countries, making necessary their identification because of it greater resistance. The aims of our study were to evaluate the performance of the chromogenic medium Agar Cromocandida and the traditional germ test tube for the presumptive identification of strains of Candida spp. collected from vaginal specimens. Of 104 yeast isolates evaluated, 77 (74%) corresponded to C. albicans, 23 (22.1%) to C. glabrata, 3 (2.9%) to C. tropicalis and one to C. parapsilosis. Agar Cromocandida identified adequately 95.2% of the yeast strains. The medium performed better for the presumptive diagnosis of C. albicans, identifying 97.4% isolates of this species, while the usefulness of the medium for C. glabrata identification was only 86.9%. The germ test tube identified correctly 97/104 (93.2%) strains as Candida albicans and Candida non-albicans. In conclusion, Agar Cromocandida may facilitate the rapid differentiation of C. albicans from Candida spp. in vaginal specimens, whereas for the identification of C. glabrata an additional diagnostic procedure is required. The combined use of the chromogenic medium with the germ test tube would allow identifying most C. albicans strains